2012
DOI: 10.1088/1748-3182/7/3/036004
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic pressure sensing with an artificial lateral line in steady and unsteady flows

Abstract: With the overall goal being a better understanding of the sensing environment from the local perspective of a situated agent, we studied uniform flows and Kármán vortex streets in a frame of reference relevant to a fish or swimming robot. We visualized each flow regime with digital particle image velocimetry and then took local measurements using a rigid body with laterally distributed parallel pressure sensor arrays. Time and frequency domain methods were used to characterize hydrodynamically relevant scenari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
96
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(97 citation statements)
references
References 32 publications
1
96
0
Order By: Relevance
“…Further wake navigation algorithms have been previously developed based on the predicted pressure signal [14]. Research by Venturelli et al [15] sampled a KVS using two symmetric linear lateral lines running on either side of a three-dimensional 'boat-shaped' craft, as an analogue of the posterior lateral line. Characterization of the KVS was performed using calculations of turbulence intensity and vortex shedding frequency (VSF) and by measuring the magnitude of the fluctuations present in the sensor readings.…”
Section: Introductionmentioning
confidence: 99%
“…Further wake navigation algorithms have been previously developed based on the predicted pressure signal [14]. Research by Venturelli et al [15] sampled a KVS using two symmetric linear lateral lines running on either side of a three-dimensional 'boat-shaped' craft, as an analogue of the posterior lateral line. Characterization of the KVS was performed using calculations of turbulence intensity and vortex shedding frequency (VSF) and by measuring the magnitude of the fluctuations present in the sensor readings.…”
Section: Introductionmentioning
confidence: 99%
“…Our results showed that periodic turbulence (KVS) can be detected by simply monitoring the pressure readings in the nose of the robot. As opposed to the spectral and turbulence analyses proposed in [21], this method works in real time owing to the very fast response and the very distinctive change in pressure readings at the nose when entering the KVS. If the change is caused solely by the changing speed of the uniform flow, then there will also be difference in the pressure on the sides of the robot, making the identification of those two different events possible.…”
Section: Discussionmentioning
confidence: 99%
“…Several types of artificial superficial MEMS-based neuromasts have been developed [18,19] and demonstrated to be capable of detecting hydrodynamic events, such as a dipole source [20]. Pressure sensors [21] or optical flow sensors placed in artificial canals [22] have been also used, and it is demonstrated that the presence of KVS can be detected and the position of the cylinder generating the street can be estimated from those sensor readings [21].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies investigated this issue [51,82]. However, experiments were done mainly in open frame flow tanks.…”
Section: Cross-correlation Flow Metering: Estimated Bulk Flow Rates Fmentioning
confidence: 99%